Bog bodies ebook - Shalvey, Declan (Bog Bodies., 2020)
An Irish gangster on the run after a job gone wrong stumbles upon a young woman lost in the Dublin mountains. Injured and unarmed, the unlikely pair must try to evade their pursuers and survive the desolate bog that has served as a burial ground for unspeakable murder throughout history. DECLAN SHALVEY (INJECTION, SAVAGE TOWN) and GAVIN FULLERTON (Bags) deliver a cold and poignant story of crime, survival, and regret.